(untitled) (Research, Society and Development, 2024)
Introduction: The Brazilian Air Force is a military institution that is part of the armed forces responsible for the security and control of the national airspace. For the exercise of military functions, Officers need good physical fitness, which is the expression of the state of physical and mental health that enables them to carry out the functional activities of the military positions of the rank, staff and category to which they belong. Objective: to compare the physical fitness of the volunteers before and after the first month of the Adaptation Internship at Base Aérea de Fortaleza in the State of Ceará. Methodology: This is a quantitative, observational analytical study. The sample consisted of 12 volunteers of both genders with an average age of 36 years. The interns were submitted to an adaptation stage lasting two months, the averages of the physical tests before and after thirty days were compared. Results: Significant statistical differences (P<0.05) were identified between the means of the arm flexion, abdominal, and 12-minute running tests. A statistically significant increase in the aerobic capacity estimated by Vo2max was observed. Conclusion: The routine imposed on the Interns in the first 30 days in the Adaptation Internship at the Fortaleza Air Force Base triggered enough physiological changes to promote better performance in the physical tests.